2019
DOI: 10.1111/jne.12751
|View full text |Cite
|
Sign up to set email alerts
|

The selective oestrogen receptor modulator, bazedoxifene, mimics the neuroprotective effect of 17β‐oestradiol in diabetic ischaemic stroke by modulating oestrogen receptor expression and the MAPK/ERK1/2 signalling pathway

Abstract: Because neuroprotection in stroke should be revisited in the era of recanalisation, the present study analysed the potential neuroprotective effect of the selective oestrogen receptor modulator, bazedoxifene acetate (BZA), in an animal model of diabetic ischaemic stroke that mimics thrombectomy combined with adjuvant administration of a putative neuroprotectant. Four weeks after induction of diabetes (40 mg kg -1 streptozotocin, i.p.), male Wistar rats were subjected to transient middle cerebral artery occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“… 4 , 15 Some earlier studies have found that the level of phosphorylated MAPK changes in the brain tissue after stroke, and the phosphorylated MEK activates the downstream kinase ERK1/2, which in turn initiates the downstream pathway to regulate cell growth, differentiation, and other physiological and pathological processes by activating CREB and subsequently modifying BDNF. 12 , 20 , 29 Burguete et al 20 confirmed that ischemia/reperfusion enhanced the activity of the MAPK/ERK1/2 signaling pathway and markedly increased the phosphorylation of ERK1/2. Wang et al 29 and other studies also indicate that the MEK-ERK1/2 pathway could be activated after cerebral ischemia in rats, and by intervening the MEK-ERK1/2 pathway could alleviate the apoptosis and inflammatory reaction of ischemic rats.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“… 4 , 15 Some earlier studies have found that the level of phosphorylated MAPK changes in the brain tissue after stroke, and the phosphorylated MEK activates the downstream kinase ERK1/2, which in turn initiates the downstream pathway to regulate cell growth, differentiation, and other physiological and pathological processes by activating CREB and subsequently modifying BDNF. 12 , 20 , 29 Burguete et al 20 confirmed that ischemia/reperfusion enhanced the activity of the MAPK/ERK1/2 signaling pathway and markedly increased the phosphorylation of ERK1/2. Wang et al 29 and other studies also indicate that the MEK-ERK1/2 pathway could be activated after cerebral ischemia in rats, and by intervening the MEK-ERK1/2 pathway could alleviate the apoptosis and inflammatory reaction of ischemic rats.…”
Section: Discussionmentioning
confidence: 95%
“…The results of this study showed that pMEK1/2, pERK1/ 2, and pCREB proteins were highly expressed in the ischemic cortex of rats in the model group, which was consistent with previous results. 12,20,29,30 Compared with the sham group, the apoptosis of nerve cells and mNSS increased dramatically, and it prompts that CIRI can activate the MEK-ERK-CREB signaling pathway. After treatment with CH-I, the expression of pMEK1/2, pERK1/2, and pCREB were decreased, and the apoptosis and nerve function injury were alleviated compared with the model group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, research has revealed multiple neuroprotective effects of BZA in various central nervous system (CNS) injury models. Specifically, BZA has been shown to reduce ischemic brain damage and apoptosis by modulating the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK)1/2 and phosphatidylinositol 3kinase (PI3K)/protein kinase B (AKT) signaling pathways [19,20]. Moreover, BZA has been found to attenuate impaired cognitive function and increased blood-brain barrier (BBB) permeability by modulating inflammation via MAPK pathway suppression in a traumatic brain injury (TBI) model [21].…”
Section: Introductionmentioning
confidence: 99%